The Polyphony of Saint Martial and Santiago de Compostela - Karp, Theodore (Oxford Clarendon Press New York Oxford University Press, 1992)
Theodore Karp proposes a fundamental reinterpretation of two major repertories of twelfth-century sacred music, that associated with the long-destroyed abbey of Saint Martial de Limoges and the manuscript preserved in the Cathedral Archive of Santiago de Compostela. Together, these comprise the most important collection of polyphonic music before the celebrated School of Notre Dame.Scholars have disagreed about the rules for transcribing this early medieval music. Karp's commentary in Volume One, along with an edition of the music in Volume Two, offers a new set principles for the understanding of its harmony, rhythm, notation, and text underlay. Professor Karp's interpretation, though likely to prove controversial, is scrupulously and convincingly defended. The transcriptions themselves will be welcomed by performing musicians, to whom an important repertory now becomes readily available.
vol. 1: Text -- vol. 2: Edition
Includes bibliographical references (v. 1, p. [221]-226) and indexes.
Keywords: Music history; Music criticism; Polyphony; Vocal music; Religion; Limoges (France); Santiago de Compostela (Spain)